STUDYING THE IMPACT OF THE SCIENTIFIC MIRACLES OF THE HOLY QURAN ON THE PHENOTYPIC AND GENETIC INDICATORS OF SOME PATHOGENIC BACTERIAL ISOLATES - Alsugmiany, Rafea zaidan mukhlif; Salih, Riyam ameen; Alwan, Asmaa Abdulkareem; Alwan, Maryam AbdulKareem (Journal of Medical Genetics and Clinical Biology, 2024)
Background : This study explores the novel application of the Holy Qur'an and Shariah ruqyah in affecting the genome of bacteria. Conducted for the first time in Iraq and the Arab world, this research seeks to investigate the potential impact of these treatments on bacterial DNA, leveraging RAPD-PCR markers for mutation detection. Materials and Methods : Genomic DNA was extracted from four bacterial isolates using established protocols. The study employed 10 RAPD primers to identify mutations in the bacterial genomes. The bacterial samples were subjected to treatments with the Qur'an and Shariah ruqyah, and the resulting genomic changes were analyzed. RAPD-PCR reactions were conducted, and the products were separated on agarose gel electrophoresis. The mutations were identified by comparing the banding patterns of treated samples with control samples. Results and Discussion : The results indicated significant genomic alterations in the bacterial samples treated with the Qur'an and Shariah ruqyah. Staphylococcus hemolyticus exhibited the highest number of mutant bands (29) compared to the control sample, followed by Proteus bacteria (25), another strain of Staphylococcus hemolyticus (22), and Staphylococcus aureus (10). These findings demonstrate the high efficiency of RAPD markers in detecting mutations with a limited number of primers. The study revealed that the magnetic field significantly affects the genome of faba beans, causing mutations that increase with longer exposure periods. The induced mutations could potentially be utilized to improve antibiotic quality and track harmful bacterial genes, rendering them non-pathogenic. The differences in results between the strains are attributed to their different genomic backgrounds, originating from various sources. Conclusions : The findings underscore the significant impact of the Qur'an and Shariah ruqyah on bacterial genomes, suggesting their potential use as alternative therapeutic methods. The study recommends applying this approach to other pathogenic bacterial species, using specialized primers for gene-specific investigations, and integrating Qur'anic and Shariah-based treatments in medical practices. Additionally, the research emphasizes the importance of employing genetic techniques to enhance bacterial species diagnosis and determine antibiotic resistance. This pioneering study paves the way for future investigations into the interplay between religious practices and genetic modifications in microorganisms, highlighting the absence of prior literature on this subject within the region.